Desenvolvimento de recobrimento submicrométrico de óxido de nióbio para aplicação em tubulações de prospecção de petróleo - Destro, Fabrício Benedito [UNESP] (2015)
In this work is presented a study on the production and physical and chemical characterization and morphology of niobium oxide (Nb2O5) thin films, obtained by the spin-coating technique, seeking electrochemical and corrosion properties superior in comparison with the materials currently existing. Also, quantitative and qualitative studies were realized to evaluate such properties, simulating the application in the offshore oil & gas industry. The first step in this study was to realize the fabrication of such films using the polymeric precursor method, using a niobium citrate precursor solution applied by the spin-coating technique, followed by a heat treatment of 300 °C for 1 hour and 650 °C for 2 hours. To characterize the thin film and to confirm the presence of niobium oxide, were used the techniques of scanning electron microscopy (SEM) with chemical composition evaluation by X-ray dispersive energy (EDX), X-ray diffraction (XRD), X-photoelectrons spectroscopy (XPS) and roughness analysis by using optical microscpy in confocal mode. The electrochemical analysis consisted in cyclic polarization tests and, later, electrochemical impedance spectroscopy (EIS), comparing different conditions of the thin film coating. The thin films were deposited initially in ABNT 4130 steel substrates and posteriorly in an API 5L X80 substrate. Taking into account that the 4130 substrates presented change of color on the surface after annealing, high atmospheric corrosion rate and lack of repeatability in the cyclic polarization tests to evaluate electrochemical properties, it was decided to deposit the films in API 5L X80 steel substrates to minimize such effects. It was verified that with the change of substrate, the effect of color change was reduced as well as the atmospheric corrosion rate, although the electrochemical teste continued with low repeatability ... (Complete abstract click electronic access below)